2021
DOI: 10.1007/s40820-021-00686-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte/Structure-Dependent Cocktail Mediation Enabling High-Rate/Low-Plateau Metal Sulfide Anodes for Sodium Storage

Abstract: As promising anodes for sodium-ion batteries, metal sulfides ubiquitously suffer from low-rate and high-plateau issues, greatly hindering their application in full-cells. Herein, exemplifying carbon nanotubes (CNTs)-stringed metal sulfides superstructure (CSC) assembled by nano-dispersed SnS2 and CoS2 phases, cocktail mediation effect similar to that of high-entropy materials is initially studied in ether-based electrolyte to solve the challenges. The high nano-dispersity of metal sulfides in CSC anode underli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The excellent electrochemical performance of Ti 3 C 2 T x /MS y //NVP systems compared with that of other full-cell devices reconfirms the great application prospect of Ti 3 C 2 T x /MS y anode and the generality of the raised strategy (Figure 7f and Table S4, Supporting Information). [5,7,13,25,38,47,57,65,66]…”
Section: Resultsmentioning
confidence: 99%
“…The excellent electrochemical performance of Ti 3 C 2 T x /MS y //NVP systems compared with that of other full-cell devices reconfirms the great application prospect of Ti 3 C 2 T x /MS y anode and the generality of the raised strategy (Figure 7f and Table S4, Supporting Information). [5,7,13,25,38,47,57,65,66]…”
Section: Resultsmentioning
confidence: 99%
“…In hexagonal layered materials, the lattice constant a represents the distance between transition metal ions and the lattice constant c represents the distance between transition metal layers. 34 In the octahedron coordination, since the size of Mg 2+ (0.72 Å) is slightly larger than that of Ni 2+ (0.69 Å), the lattice parameters increase after Mg ion replacement. The Rietveld method was used to refine the data, 35 which increased the distance between transition metal ions and transition metal layers, indicating that Mg 2+ entered the transition metal position.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Supporting Information Table S2 shows information on the Rietveld refined lattice parameters and detailed structures. In hexagonal layered materials, the lattice constant a represents the distance between transition metal ions and the lattice constant c represents the distance between transition metal layers . In the octahedron coordination, since the size of Mg 2+ (0.72 Å) is slightly larger than that of Ni 2+ (0.69 Å), the lattice parameters increase after Mg ion replacement.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, introduction of intrinsic highly conductive and high theoretical capacity heterogeneous components such as Fe 9 S 10 , Sb 2 S 3 , and NiS 2 can considerably increase the conductivity of MoS 2 and accelerate the reaction kinetics of sodium ions. 26,[44][45][46][47][48][49] For instance, heterostructure Sb 2 S 3 / MoS 2 , 15 MnS-MoS 2 , 25 Bi 2 S 3 /MoS 2 , 44 Ni 3 S 2 @MoS 2 , 50 and SnS-MoS 2 51 have been reported that can deliver high electrochemical performance. Besides metal sulfide composition, low-cost carbonaceous materials have also been comprehensively used to embellish anode materials due to their good electric conductivity, which can improve energy storage properties.…”
Section: Introductionmentioning
confidence: 99%